If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + k = 3k + -1 Reorder the terms: 1 + k = -1 + 3k Solving 1 + k = -1 + 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. 1 + k + -3k = -1 + 3k + -3k Combine like terms: k + -3k = -2k 1 + -2k = -1 + 3k + -3k Combine like terms: 3k + -3k = 0 1 + -2k = -1 + 0 1 + -2k = -1 Add '-1' to each side of the equation. 1 + -1 + -2k = -1 + -1 Combine like terms: 1 + -1 = 0 0 + -2k = -1 + -1 -2k = -1 + -1 Combine like terms: -1 + -1 = -2 -2k = -2 Divide each side by '-2'. k = 1 Simplifying k = 1
| -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 | | 4=p-1 | | X-1.25=3.5 | | 0.5-0.5j=0 | | 2(h+3)+1=9 | | 0=-9(b-1) | | x^2+3-12=0 | | 12x^3-8x^2-35x+6=0 | | (2x+4)(x)=20 | | X+0.3=-0.4 | | -6.75=x+5.4 | | 4(2x+4)=10x+15-2x+17 | | 265=-5x | | 14=k+9 | | 5-6w=-13 | | 9x-2+55=13+14x | | -4x-36=-72 | | -16+m=-20 | | 5=9+4x | | 0.5(4x+8)(x)=20 | | 4c=16.8 | | -19=x-17 | | 6y-(2y-5y)=29 | | 1.48(k+3)=5.92 | | b+14=1 | | d+(-7)=12 | | 6x+3=98-3x+6 | | 7+1-6x+3x=3x-5x | | q+6.44=0.72 |